Automation Assemblages in the Internet of Things: Discovering Qualitative Practices at the Boundaries of Quantitative Change - Novak, Thomas P; Hoffman, Donna L (Journal of Consumer Research, 2023)
Abstract We examine consumers’ interactions with smart objects using a novel mixed-method approach, guided by assemblage theory, to discover the emergence of automation practices. We use a unique text data set from the web service IFTTT, (“If This Then That”), representing hundreds of thousands of applets that represent “if–then” connections between pairs of Internet services. Consumers use these applets to automate events in their daily lives. We quantitatively identify and qualitatively interpret automation assemblages that emerge bottom-up as different consumers create similar applets within unique social contexts. Our data discovery approach combines word embeddings, density-based clustering, and nonlinear dimensionality reduction with an inductive approach to the thematic analysis. We uncover 127 nested automation assemblages that correspond to automation practices. Practices are interpreted in terms of four higher-order categories: social expression, social connectedness, extended mind, and relational AI. To investigate the future trajectories of automation practices, we use the concept of the possibility space, a fundamental theoretical idea from assemblage theory. Using our empirical approach, we translate this theoretical possibility space of automation assemblages into a data visualization to predict how existing practices can grow and new practices can emerge. Our new approach makes conceptual, methodological, and empirical contributions with implications for consumer research and marketing strategy.